First report of tuberculosis in a cat from Italy caused by Mycobacterium africanum, lineage 6: genomic characterization and phylogenetic analysis - Alba, Patricia; Caprioli, Andrea; Cocumelli, Cristiano; Eleni, Claudia; Galietta, Valentina; Giacomi, Angelo; Sorbara, Luigi; Stravino, Fiorentino; Feltrin, Fabiola; Amoruso, Roberta; Ianzano, Angela; Ceccaroni, Francesco; et al. (Frontiers in Microbiology, 2025)
IntroductionTuberculosis in humans is mainly caused by two closely related bacteria within the Mycobacterium tuberculosis complex (MTBC), which are Mycobacterium tuberculosis and Mycobacterium africanum. M. tuberculosis is widely spread, while M. africanum is more ecologically restricted to Africa.Methods and resultsIn 2023, we examined a skin biopsy from a 3-year-old female domestic cat with multifocal nodular cutaneous lesions and respiratory problems. The animal was an indoor cat kept in Rome, reportedly taken in as a stray kitten from a village in southern Italy (Central Calabria Region). Skin histology with Ziehl–Neelsen staining was consistent with suspected mycobacteriosis. Bacterial cultures for Mycobacterium spp. yielded an isolate, identified by polymerase chain reaction (PCR) as a Mycobacterium tuberculosis complex (MTBC). Whole-genome sequencing and bioinformatics further identified the isolate as M. africanum lineage 6, and phylogeny with 634 other MTBC genomes placed it within a West African cluster (mainly from Gambia) of the L6.1.2 sublineage. Resistome analysis indicated the presence of resistance genes intrinsic in M. tuberculosis and point mutations not associated with resistance. The cat died roughly 1 year later, most probably from systemic tuberculosis, but the owner did not request a necropsy.DiscussionThis represents the first reported case of M. africanum infection in a carnivore and in a companion animal. The case history reports a stray kitten collected in an area of southern Italy, near the first migrant reception centers and croplands where workers coming from West Africa are often employed, consistent with our phylogenetic evidence.